PERHITUNGAN KEMAUAN UNTUK MEMBAYAR PADA PENETAPAN NILAI KESELAMATAN TRANSPORTASI JALAN UNTUK KELOMPOK PENGGUNA JALAN TERTENTU - Tjahjono, Tri; Hendratmoko, Pungkas (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Several studies on value of road safety (VRS) has been widely applied in various countries .One approach that is commonly used to valuation of road safety is to measure public willingness to pay ( WTP ) in order to increase the safety aspect. In this model preferences are based on the behavioral theory of economics perspective that explains that every human behavior based on the preferences . The basic premise of this theory explains that every human being has a preference for a number of goods. The issue of safety is included in the category of non-market goods that are not traded and often occurs refusal of the respondent to answer direct questions about WTP, therefore to obtain objective answers from respondents, WTP design questions need to be linked with other proxies. The purpose of this study was to calculate the WTP on valuation of road safety for specific communities to redesign the WTP questions associated with the proxy vehicle maintenance and health maintenance.